2022
DOI: 10.1186/s43058-022-00279-1
|View full text |Cite
|
Sign up to set email alerts
|

Core components of a Community of Practice to improve community health worker performance: a qualitative study

Abstract: Background Communities of Practice (CoPs) offer an accessible strategy for healthcare workers to improve the quality of care through knowledge sharing. However, not enough is known about which components of CoPs are core to facilitating behavior change. Therefore, we carried out a qualitative study to address these important gaps in the literature on CoPs and inform planning for an interventional study of CoPs. Methods We organized community health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The PR is also more in line with a community of practice than a traditional learning and development model. It encourages members to bring their engagement examples for discussion, and the emphasis is on collaboration, mutual learning and community 28. The supporting Teams channel with a filing system of resources for different phases of engagement, downloadable recordings of each session, accompanying notes and the interactive discussion board, create additional ways for members to participate, learn and share their consumer engagement experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The PR is also more in line with a community of practice than a traditional learning and development model. It encourages members to bring their engagement examples for discussion, and the emphasis is on collaboration, mutual learning and community 28. The supporting Teams channel with a filing system of resources for different phases of engagement, downloadable recordings of each session, accompanying notes and the interactive discussion board, create additional ways for members to participate, learn and share their consumer engagement experiences.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed for a collaborative relationship shown to be key in previous studies. In Uganda, 8 LHWs in two tuberculosis clinics formed a community of practice [33]. In qualitative interviews, LHWs identified activities as core to improving the quality of their work: (1) individual review of performance, (2) collaborative improvement meetings, (3) real-time communications among members, (4) didactic education sessions, and (5) clinic-wide staff meetings.…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of construct validity of the adapted General Self-Efficacy Scale. We selected five validation constructs based on previous validation studies of the General Self-Efficacy Scale (Luszczynska et al, 2005) and qualitative studies on community health worker self-efficacy in Uganda (Hennein et al, 2021(Hennein et al, , 2022Ochom et al, 2018). We collected concurrent measures of years of experience, social support, educational attainment, and depressive symptoms to assess convergent validity, and age to assess discriminant validity.…”
Section: Response Optionsmentioning
confidence: 99%
“…Community health workers reported that their self-efficacy was dependent on their previous experiences (i.e., performance accomplishments), and community health workers with less experience reported relying on advice and "empowerment" from more experienced community health workers to facilitate their work (i.e., vicarious experiences and verbal persuasion) (Ndejjo et al, 2020). Other studies have also shown that community health worker selfefficacy is important to facilitate sustained motivation in health programs (Bhatnagar et al, 2017;Gopalan et al, 2012;Hennein et al, 2022;Sarin & Lunsford, 2017). For example, in a mixed-methods study of community health workers in India, the authors found that community health worker self-efficacy was significantly associated with individual motivation in multivariable models (Gopalan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation